Labor supply elasticities in Europe and the US - Olivier Bargain; Kristian Orsini; Andreas Peichl (Institute for the Study of Labor (IZA), 2011)
Despite numerous studies on labor supply, the size of elasticities is rarely comparable across countries. In this paper, we suggest the first large-scale international comparison of elasticities, while netting out possible differences due to methods, data selection and the period of investigation. We rely on comparable data for 17 European countries and the US, a common empirical approach and a complete simulation of tax-benefit policies affecting household budgets. We find that wage-elasticities are small and vary less across countries than previously thought, e.g., between .2 and .6 for married women. Results are robust to several modeling assumptions. We show that differences in tax-benefit systems or demographic compositions explain little of the cross-country variation, leaving room for other interpretations, notably in terms of heterogeneous work preferences. We derive important implications for research on optimal taxation.
urn:nbn:de:101:1-201107042691
Keywords: C25; C52; H31; J22; 330; household labor supply; elasticity; taxation; Europe; US